Pharmacokinetic-interaction of Vitex negundo Linn. & paracetamol - Tripathi Y.B.; Tiwari O.P.; Nagwani S.; Mishra B. (My University, 2025)
Background & objectives: Currently, herbal preparations are clinically used as functional food, food supplements or as add on therapy, which affects the bioavailability and also the net therapeutic potential of co-administered allopathic drugs. Therefore, it is important to assess the interaction among these two classes of drugs. Here we studied the interaction between orally-administered ethanolic extract of leaves of Vitex negundo Linn. (Verbenaceae) (VN extract) and paracetamol in albino rats. Method: Solvent free dried extract of VN leaves was orally given to experimental rats in different doses (62.5-1000 mg/kg/b.wt.), daily for six consecutive days. On days 3 and 6, paracetamol (100 mg/kg/b.wt.) was orally administered to these extract treated rats and control rats (drug vector). At various time intervals (5 min - 120 min), blood was collected from each animal and paracetamol concentration was determined in plasma by using HPLC with UV detector at 249 nm. Various pharmacokinetic parameters were calculated by non compartmental model. Results: A significant decline in plasma concentration of paracetamol with time-gap was recorded with the increasing dose of VN extract, without affecting its Tmax (maximum time to achieve peak plasma concentration). There was a significant decrease in the extent of absorption and decline in intensity of therapeutic response (as evidenced by reduced AUC value and decline in Cmax). Further, compared to control, the relative bioavailability of paracetamol, in presence of VN extract, decreased significantly. Interpretation & conclusions: VN extract or its ayurvedic formulation if co-administered with allopathic drug like paracetamol, the dose of allopathic drug needs to be adjusted in order to achieve desired therapeutic response of paracetamol.